Phenotype and natural history of elderly onset inflammatory bowel disease: a multicentre, case‐control study. Issue 5 (25th January 2018) - Mañosa, M.; Calafat, M.; de Francisco, R.; García, C.; Casanova, M. J.; Huelín, P.; Calvo, M.; Tosca, J.; Fernández‐Salazar, L.; Arajol, C.; Zabana, Y.; Bastida, G.; et al.
Summary: Background: Onset during old age has been reported in upto 10% of total cases of inflammatory bowel disease (IBD). Aim: To evaluate phenotypic characteristics and the use of therapeutic resources in patients with elderly onset IBD. Methods: Case‐control study including all those patients diagnosed with IBD over the age of 60 years since 2000 who were followed‐up for >12 months, identified from the IBD databases. Elderly onset cases were compared with IBD patients aged 18 to 40 years at diagnosis, matched by year of diagnosis, gender and type of IBD (adult‐onset). Results: One thousand three hundred and seventy‐four elderly onset and 1374 adult‐onset cases were included (62% ulcerative colitis (UC), 38% Crohn's disease (CD)). Among UC patients, elderly onset cases had a lower proportion of extensive disease (33% vs 39%; P < 0.0001). In CD, elderly onset cases showed an increased rate of stenosing pattern (24% vs 13%; P < 0.0001) and exclusive colonic location (28% vs 16%; P < 0.0001), whereas penetrating pattern (12% vs 19%; P < 0.0001) was significantly less frequent. Regarding the use of therapeutic resources, there was a significantly lower use of corticosteroids ( P < 0.0001), immunosuppressants ( P < 0.0001) and anti‐TNFs agents ( P < 0.0001) in elderly onset cases. Regarding surgery, we found a significantly higher surgery rate among elderly onset UC cases (8.3% vs 5.1%; P < 0.009). Finally, elderly onset cases were characterised by a higher rate of hospitalisations (66% vs 49%; P < 0.0001) and neoplasms (14% vs 0.5%; P < 0.0001). Conclusions: Elderly onset IBD shows specific characteristics and they are managed differently, with a lower use of immunosuppressants and a higher rate of surgery in UC. Abstract : Linked Content This article is linked to Everhov et al and Mañosa and Domènech papers. To view these articles visithttps://doi.org/10.1111/apt.14598 andhttps://doi.org/10.1111/apt.14622 .